Gut microbiota differences in stunted and normal-lenght children aged 36-45 months in East Nusa Tenggara, Indonesia. - Ingrid S Surono; Ilia Popov; Sanne Verbruggen; Jessica Verhoeven; Pratiwi D Kusumo; Koen Venema (PLoS ONE, 2024)
The role of the gut microbiota in energy metabolism of the host has been established, both in overweight/obesity, as well as in undernutrition/stunting. Dysbiosis of the gut microbiota may predispose to stunting. The aim of this study was to compare the gut microbiota composition of stunted Indonesian children and non-stunted children between 36 and 45 months from two sites on the East Nusa Tenggara (ENT) islands. Fecal samples were collected from 100 stunted children and 100 non-stunted children in Kupang and North Kodi. The gut microbiota composition was determined by sequencing amplicons of the V3-V4 region of the 16S rRNA gene. Moreover, fecal SCFA concentrations were analyzed. The microbiota composition was correlated to anthropometric parameters and fecal metabolites. The phyla Bacteroidetes (Bacteroidota; q = 0.014) and Cyanobacteria (q = 0.049) were significantly higher in stunted children. Three taxa at genus levels were consistently significantly higher in stunted children at both sampling sites, namely Lachnoclostridium, Faecalibacterium and Veillonella (q < 7 * 10-4). These and 9 other taxa positively correlated to the z-score length-for-age (zlen), while 11 taxa negatively correlated with zlen. Several taxa also correlated with sanitary parameters, some of which were also significantly different between the two groups. All three fecal SCFA concentrations (acetate, propionate and butyrate) and their total were lower in stunted children compared to non-stunted children, although not significant for butyrate, indicating lower energy-extraction by the gut microbiota. Also, since SCFA have been shown to be involved in gut barrier function, barrier integrity may be affected in the stunted children. It remains to be seen if the three taxa are involved in stunting, or are changed due to e.g. differences in diet, hygiene status, or other factors. The observed differences in this study do not agree with our previous observations in children on Java, Indonesia. There are differences in infrastructure facilities such as clean water and sanitation on ENT and Java, which may contribute to the differences observed. The role of the gut microbiota in stunting therefore requires more in depth studies. Trial registration: the trial was registered at ClinicalTrials.gov with identifier number NCT05119218.